2008
DOI: 10.1002/dc.20934
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration cytology of Castleman disease: Case report with review of the literature

Abstract: Organs involved by Castleman disease (CD) may be investigated by fine-needle aspiration cytology. No specific cytomorphological criteria are currently described for a definitive diagnosis. The cytological features of three fine-needle aspirations from three different lymph nodes of a patient with histologically confirmed CD of the hyaline-vascular type are herein reported, with a review of the literature. The fine-needle aspirations showed branching capillaries associated with fragments of germinal center. Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…However, FNA remains rather underutilized for the evaluation of lymphadenopathy, partially due to the lack of available expertise for the performance and interpretation of such samples (21). Several authors have emphasised the diagnostic importance of FNC in CD (35,36). Although only case reports are available in the literature, attempts have been made to describe the cytomorphological findings in CD (37-42) which can be indicative enough for it to be considered preoperatively, among other entities.…”
Section: Discussionmentioning
confidence: 99%
“…However, FNA remains rather underutilized for the evaluation of lymphadenopathy, partially due to the lack of available expertise for the performance and interpretation of such samples (21). Several authors have emphasised the diagnostic importance of FNC in CD (35,36). Although only case reports are available in the literature, attempts have been made to describe the cytomorphological findings in CD (37-42) which can be indicative enough for it to be considered preoperatively, among other entities.…”
Section: Discussionmentioning
confidence: 99%
“…[8] to a set of cytomorphological criteria that could help in the identification of this condition on aspirate smears. After review, the following cytomorphological criteria were suggested to be indicators of the lesion: (i) The presence of large oval to round cells having ill-defined cytoplasmic margins and large nuclei with irregular nuclear outlines having fine or coarse chromatin, giving a crumpled tissue paper appearance; (ii) a polymorphous population of lymphoid cells predominantly of small lymphocytes in the background.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that although hyaline-vascular CD is a difficult diagnostic entity on aspirate material, the presence of large histiocytic cells with a crumpled tissue paper appearance of the nuclei in a background of small lymphocytes is a useful indicator for suspecting this lesion. [8] However, these findings should be analyzed in larger studies to determine if they could in anyway reduce the diagnostic dilemma in cases of CD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Further, a lesser degree of the enhancement is found in the plasma cell variant. [13] CT-guided fine-needle aspiration (FNA) of the mass is usually nondiagnostic in both UCD and MCD and are frequently “negative for malignant cells.”[291011] According to Deschênes et al .,[14] FNA can be useful in diagnosing some cases of CD, but in author's opinion, excision biopsy should be preferred whenever possible.…”
mentioning
confidence: 99%